Konfigurasi Kepemimpinan Nasional Perspektif Pluralisme Agama di Indonesia - Yusdani - (Universitas Islam Indonesia, 2004)
The public election 2004 denotes the moment of history for developing future Indonesia. In this sense, the public election can be called as a chance to end the national leadership crisis. The succession of national leadership and in order to Indonesian people choose national leader who including qualification and able to bring this nation toward change. For that reason, it is important to formuiate the critena of national leader. Because of Indonesia nation is pluralisticnation either in term of religion, cultural background or etc. Sothat, the national leader that Indonesian people need is inclucive, pluralist and dialogist leader.